PENGARUH BELANJA MODAL, UMUR PERUSAHAAN, PERTUMBUHAN, DAN RASIO UTANG TERHADAP PENGUNGKAPAN EMISI KARBON DAN REAKSI SAHAM - Iqbal Mohamad Dwinanda; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
The purpose of this study was to examine the effect of capital expenditure, firm age, growth, and debt ratio on disclosure of carbon emissions and stock reaction in manufacturing companies in Indonesia. The population in this study consisted of manufacturing companies in the Indonesia Stock Exchange for the period 2013 - 2017 that publish annual reports and disclose carbon emissions. Sampling is done using the purposive sampling method. The total sample of this study was 36 companies. This study uses multiple regression analysis to test hypotheses. The results of this study indicate that variable of capital expenditure has a significant positive effect on carbon emission disclosure. Meanwhile the variables of firm age, growth, and debt ratio have not a significant effect on carbon emission disclosure and stock reaction.